VALPROIC ACID INTERFERENCE IN ABDOMINAL WALL TISSUE REPAIR: POTENTIAL IMPLICATIONS FOR HERNIA AND LAPAROTOMY SURGERIES - Louro de Hollanda, Marcos; Pedro do Valle Varela, João; Victória Bahia Silva, Maria; Meira Fernandes Costa, Nicole; Gonçalves Martins, Kelli; Fagundes Cardoso, Melissa; Martins Pinto, Juliana; Beatriz Dias Induzzi, Luiza; Garcia de Azevedo Castro, Gabriel; de Oliveira Camara, Leandro; Alves Brambilla, Bernardo; do Valle Risso, Giulia (Health and Society, 2025)
Valproic acid (AVP) is widely used in the treatment of epilepsy and mood disorders, but recent studies suggest that its epigenetic action may negatively interfere in tissue regeneration and healing processes. Repair of the abdominal wall, essential for the success of procedures such as herniorrhaphy and laparotomy, depends on a cascade of inflammatory, cellular and molecular events that can be modulated by systemic drugs such as AVP. The aim of this study was to analyze the interference of valproic acid in abdominal wall healing, considering its possible effects on collagen synthesis, fibroblast proliferation and the integrity of the extracellular matrix, and to discuss its clinical implications in abdominal surgery. This is a literature review with a qualitative and exploratory approach. The studies were selected using the PubMed, SciELO, ScienceDirect and Scopus databases, with full articles published in peer-reviewed scientific journals addressing the use of valproic acid in the context of tissue healing, especially in patients undergoing surgical procedures. The time frame of the research considered the period from 2018 to 2022, based on the oldest article (Costa et al., 2018) and the most recent (Santos et al., 2022; Alves et al., 2022; Moura et al., 2022). The findings indicate that AVP, by acting as a histone deacetylase (HDAC) inhibitor, can alter the gene expression of key proteins in the healing process, such as type I and III collagen, metalloproteinases and growth factors. In experimental models, delayed granulation tissue formation and collagen matrix organization were observed, suggesting an increased risk of dehiscence, incisional hernia and abdominal wall fragility in patients taking the drug continuously. We conclude that valproic acid may represent an underestimated risk factor in surgical repair of the abdominal wall. Preoperative assessment of the use of this drug should be considered in clinical practice, especially in elective surgeries. New clinical studies are needed to validate these experimental findings and guide safer therapeutic approaches.